Effect of Changing Primary Fixed Sheave Angle and Roller Weight on Torque, Power, Top Speed, and Acceleration on Matic Motorcycles - Widiyatmoko; Arfan Ishartanto; Mike Elly Anitasari; Khoirul Mu'allif; Ma’rifat Al Hakim (Jurnal E-Komtek, 2022)
This study aimed to determine the effect of angle changes on the primary fixed sheave and roller mass on torque, acceleration, engine power, and top speed of automatic motorcycles. This type of research is experimental research. The subjects in this study were 125 cc automatic motorcycles modified at the angle of the primary fixed sheave and the mass of the rollers. The angles of change were 14.5˚, 13.5˚, and 12.5˚; while the change in roller mass was 14, 13, and 12 grams. The testing began with tuning up the motorbike, then installing the fixed sheave and roller primary units that have been modified to the CVT (Continuously Variable Transmission) primary drive for further testing, and collecting the data using a dyno test tool. The results of this study show that: 1) Changes made to the primary drive pulley, especially to changes in the angle of the Primary fixed sheave and the weight or mass of the roller with the application simultaneously affect the torque, acceleration, engine power, and top speed of automatic motorbikes; 2) changing the angle of the primary fixed sheave (13.5˚) with the application of a roller weight of 13 grams can increase the maximum speed (top speed) by 0.4 (Kph) compared to the standard ones; 3) the increase in power and torque resulting from changes in the primary fixed sheave and the weight of the rollers applied at the same time do not significantly increase top speed and acceleration. Conversely, low power and torque do not necessarily reduce the top speed and acceleration of automatic motorcycles.